“NEVE LUCRETIUS A ME INDEFENSUS MANEAT”: GIROLAMO MERCURIALE, IL DE RERUM NATURA E LA MEDICINA NEL RINASCIMENTO - ANDREA CECCARELLI (Lexicon Philosophicum)
The return of Lucretius’ De rerum natura in 1417 promoted an increasing recovery of ancient medical theories related to the atomistic philosophy in Renaissance Italy. Since Girolamo Fracastoro used Lucretian concept of semina rerum to explain the spread of the ‘French pox’ (1530), philosophers, physicians and humanists returned to look at Lucretius’ poem on nature as a main source of medical knowledge. This is the case of Girolamo Mercuriale, who defended Lucretius’ scientific authority first in a bitter epistolary quarrel with Piero Vettori, then in his Variarum lectionum libri (1570), where Lucretius is placed into the same atomistic tradition with Hippocrates and Asclepiades of Bithynia, the founder of the Methodic school of medicine, and finally in his treatise De pestilentia (1577), where Mercuriale exposed his theory about the contagion referring to the concepts of both Lucretius and Fracastoro.